AWARENESS OF HEALTHY LIVING THROUGH HEALTH CHECK-UPS FOR MEDAN CITY ASN - Aidha, Zuhrina; Fardani, Siti Nurhaliza; Azalia, Zalfa Naifah; Anisa, Nur; Fadiah, Nifazatil; Almira, Salwa Siti; Agustin, Annisa Marsya; Syahmala, Arya Rahman (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Health is a crucial factor in supporting the work productivity of State Civil Apparatus (ASN). However, busy schedules and high work mobility often lead ASN to neglect their health, including routine health checks. The low participation of ASN in free health checks indicates a limited awareness of the importance of early disease detection and healthy living. This study aims to analyze the level of awareness of healthy living through health checks among ASN in Medan City and to explore the work and mobility factors that influence this behavior. The approach used was descriptive qualitative, with data collected through in-depth interviews with informants from ASN in Medan City government agencies. The results showed that the majority of ASN understand the importance of maintaining health, but awareness of consistently undergoing health checks remains low. The main factors influencing this are high workloads, limited time, and the perception that physical conditions are still "healthy" so that check-ups are not considered urgent. However, some informants stated that support from the agency, easy access to services, and interesting and interactive outreach can increase their motivation to participate in healthchecks.